Farm, wholesale, and retail beef price relationship - Schroeder, Ted C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Analysis of weekly retail, wholesale, and farm beef price data indicated that a time lag exists between price changes at the various market levels. Farm-level slaughter cattle price changes typically lead wholesale beef price changes by 2 to 3 weeks. Similarly, wholesale beef price changes typically lead price changes at the retail level by 3 to 4 weeks.
Keywords: Beef; Wholesale beef prices; Retail beef prices; Farm beef prices